Impact of Local versus Systemic Progesterone Administration on Pregnancy Viability in Cases of Imminent Miscarriage - Ikram Ullah; Bhittani, Rehana; Alam, Iftikhar; Shaikh, Darakshan; Ayesha; Hassan, Neelam (Indus Journal of Bioscience Research, 2025)
Background: Threatened miscarriage is a prevalent complication in early pregnancy, affecting up to 20% of women before 20 weeks of gestation. Progesterone therapy is widely used to support early gestation, but the optimal route of administration remains a topic of ongoing research. Objective: To compare the efficacy of oral versus vaginal progesterone in the management of threatened miscarriage during the first trimester. Methods: A prospective comparative study was conducted involving 169 pregnant women diagnosed with threatened miscarriage. Group A (n=85) received oral progesterone, while Group B (n=84) received vaginal progesterone. Participants were monitored for symptom resolution and pregnancy continuation. Key parameters including age, gestational age, parity, and treatment outcomes were statistically analyzed. Results: The mean age was 30 ± 8.71 years in Group A and 32 ± 7.96 years in Group B. Oral progesterone was effective in 70 patients (82.4%), whereas vaginal progesterone was effective in 78 patients (92.9%). The difference in efficacy was statistically significant (p = 0.0305), favoring vaginal administration. Conclusion: Vaginal progesterone demonstrated a higher clinical success rate compared to oral progesterone in managing threatened miscarriage. Given its superior efficacy and localized therapeutic action, vaginal progesterone may be the preferred route for early pregnancy support, provided patient tolerance is ensured.